Sporadic Burkitt Lymphoma: A Case Report - Edgar Vargas Flores; Claudia Leticia Avitia Raygoza; Daniel Hernández Castañeda; Jorge Arturo Sánchez Garza; Juan Carlos Quintana Cortéz (Baqiyatallah University of Medical Sciences, 2019)
Introduction: Burkitt lymphoma is an aggressive subtype of Hodgkin lymphoma with a doubling time of 25 hours. It is characterized by a MYC gene coding alteration which results from a translocation of chromosome 8 on the MYC gene locus and immunoglobulin heavy-chain locus (IGH) on chromosome 14. Even though HIV infection is associated to an increased risk of Burkitt lymphoma, these type of malignancies are EBV-negative cases. Sporadic type Burkitt lymphoma is a rare clinical entity. Case Presentation: A 48-year-old female without any past medical history presented with a chief complaint of mild abdominal pain of 6 months duration located at the epigastrium which was not related to food ingestion. Nausea or vomiting were neither reported. She noted an acute increased abdominal pain over the last 4 hours before presentation, with irradiation to the right lower quadrant. She denied any Fever, night sweats and weight loss. She also reported hypermenorrhea in the last 6 months. During the physical examination, a palpable mass with 10 cm in diameter was found on right lower quadrant. Conclusion: Sporadic Burkitt lymphoma is one of the rarest hematologic malignancies. The increased tumor size may be more than enough to show clinical or biochemical abnormalities such as serum lactate dehydrogenase (LDH) increased and tumor lysis.